Feasibility, reliability, usability, and satisfaction of a digital medical device (ZEMY) for symptom management in patients treated for breast cancer: a single-arm interventional study - Luis Teixeira; Christelle Levy; David Coeffic; Rim Ghorbal; Julien Dupin; Nazario Esposito; Olfa Derbel (BMC Digital Health)
Abstract Background and methods E-health solutions are a promising tool to assist patients in self-managing symptoms for various diseases. This study aimed to assess the feasibility, reliability, usability, and satisfaction of a digital medical device (ZEMY) for patients’ self-monitoring of symptoms commonly experienced during breast cancer treatment and to enhance interaction with healthcare professionals. In this open-label, interventional, multicentre, single-arm clinical trial (NCT03558490), patients at all stages of breast cancer initiating oral and/or parenteral treatment were recruited at initiation of therapy and followed for 3 months. During treatment, the patients reported 9 symptoms (diarrhoea, nausea/vomiting, fever/febrile neutropenia, fatigue, pain, cutaneous and mucosal toxicities, hypertension, anxiety/depression) through the ZEMY application, which provided self-management recommendations and sent message alerts to healthcare professionals. To reach the primary feasibility endpoint, more than 50% of patients with one-sided 95% confidence interval (exact CI computed using Clopper-Pearson method) had to complete at least 3 symptoms entries, of which more than 60% complete until receiving a recommendation. Results Out of the 56 screened patients, 54 were included in the analysis between June 12th 2018 and January 11th 2019, and 52 completed the study. Over half of patients (31/54 [57.4%]) were feasibility responders, but this percentage was not significantly higher than the predefined minimum feasibility cut-off of 50%, as the lower limit of the one-sided 95% exact CI was 45.3%. Nonetheless, 87.0% of patients reported at least 3 symptoms with ZEMY and 66.0% had an entry completion rate ≥ 60%. Six of the 9 symptoms were reported at least once by more than 30% of the patients. The recommendations were considered relevant at least once for more than 80% of cases for each symptom. Patients were more satisfied (mean 10-point visual analogue scale score: 6.3 ± 2.9) with ZEMY than healthcare professionals (4.4 ± 1.5). The global patients’ quality of life remained stable during the study. Conclusions ZEMY provided satisfactory recommendations for the self-management of selected symptoms occurring during anti-cancer treatment and demonstrated good usability, but its feasibility was indemonstrable. Trail registration The trial was registered on June 14th 2018 at ClinicalTrails.gov (Trial Registration Number: NCT03558490).